Pengaruh corporate governance, perspektif fraud triangle, income smoothing dan karakteristik perusahaan terhadap fraud pada perusahaan manufaktur di Indonesia - Wardhana, Ismail; Usman, Bahtiar (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
The problems contained in this study are cases of fraud or fraud that still occur in companies listed on the Indonesia Stock Exchange. Corporate governance is considered as a solution to improve internal control so that it can reduce the number of fraud in the company. The purpose of this study is to analyze the effect of corporate governance, the motivation that arises through the fraud triangle theory, income smoothing, and company characteristics against fraud in companies engaged in the manufacturing sector listed on the Indonesia Stock Exchange. The research methodology used in this study is purposive sampling which produces 33 samples of companies for 5 years of research in the 2017-2021 period. The research model uses a panel of regression data that is processed using E-Views. The findings and contributions of this study are that corporate governance has a significant negative effect on fraud, income smoothing has a significant positive effect on fraud and company age has a significant negative effect on fraud. Meanwhile, the motivation to commit fraud described by the fraud triangle theory and firm size has no significant effect on fraud. The implications of this study are useful for management to determine areas that affect strengthening corporate governance in companies, reduce management aggressiveness in income smoothing actions and find out whether the level of debt ratios and changes in external auditors can increase motivation to commit fraud.